Laparoscopic therapy as a treatment for diaphragmatic endometriosis (Research, Society and Development, 2022)
Introduction: Thoracic involvement accounts for the most prevalent extrapelvic presentation of endometriosis, with the diaphragm being the region most affected by the disease. A variety of symptoms are cited in the literature, with the catamenial factor being the main differential finding of these manifestations. Objective: The purpose of this article is to describe the social impact of diaphragmatic endometriosis on the lives of patients and to discuss the description of endometriosis surgery. Methodology: The present study is based on a literature review based on articles selected by the criteria of relevance and up-to-dateness inserted in a scientific database. Results: The first report of endometriosis involving the lung parenchyma was described in 1938 by Schwarz, while in 1958 there was the first report of catamenial pneumothorax by Maurer et al. Pelvic and transvaginal ultrasound with bowel preparation and magnetic resonance imaging (MRI) with specialized protocols are the main imaging methods for detecting and staging endometriosis. Conclusion: Surgical treatment is the only curative method, and the minimally invasive route should be the choice given the lower risks of contamination, better healing, and complete rehabilitation of the patient in a shorter period if laparotomy were performed. It is worth noting that the patient needs a multidisciplinary approach aiming at a complete recovery and the return to daily activities as soon as possible.